Ontology in the light od recentivism - Zięba, Włodzimierz (Folia Philosophica, 2003)
In the article, the author deals with the problems of ontology in recentivism, where ontology plays the role of the perennial philosophy. From this perspective, the author examines the relation of ontology towards epistemology. It turns out that, having assumed the declared primacy of ontology over epistemology, the matter becomes more complicated, so the author suggests that it is hardly possible to separate these two things and give a position of prominence to one of them. The author shows the subject-object (resp. ontological-epistemological) correlation on the basis of the relationship between the one-appearance man and multi-appearance man and also on the basis of the euthyphronic (right-minded) cognition in the form of an act of the right-minded cognition. The ontological implication of departing from a right-minded act is the world’s being the world for us (cf. the anthropological consequences of recentivism). Bearing this in mind the author also examines the problem of existence itself, which in recentivism is a cognitive superstition, and the relationship between the fundamental ontology and the regional one.